Maine’s Economy: Peering into the Crystal Ball - Reilly, Catherine (Maine Policy Review, 2006)
The five economists and financial professionals who comprise Maine’s Consensus Economic Forecasting Commission (CEFC) meet twice a year to forecast the state’s economy. By statute, this forecast then is used to project state revenues and develop the state’s budget. In this article, State Economist Catherine Reilly presents the CEFC’s fall 2006 forecast for employment, income, and inflation. Although never a guarantee, this year’s forecast suggests Maine’s economic future will be one of slow and steady growth, with moderating energy prices, lower inflation, and a continued expansion of the state’s service sector.